2009
DOI: 10.2106/jbjs.h.00948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Subacromial Ropivacaine Infusion for Rotator Cuff Surgery

Abstract: We found minimal evidence to support the use of ropivacaine infusion for improving outcomes following rotator cuff surgery in the setting of preemptive ropivacaine and intraoperative parecoxib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 23 publications
0
45
0
2
Order By: Relevance
“…However, it is difficult to directly compare the present results with other studies, for important methodological differences, since to our knowledge this is the first study of local anaesthesia with either control or IBPB groups in open shoulder instability surgery [2,8,10]. In particular, the comparison with a control group in relation with IBPB, the most commonly analgesic technique used in this surgery, using the same dose and volume of anaesthetics, allow improving the analgesic considerations.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, it is difficult to directly compare the present results with other studies, for important methodological differences, since to our knowledge this is the first study of local anaesthesia with either control or IBPB groups in open shoulder instability surgery [2,8,10]. In particular, the comparison with a control group in relation with IBPB, the most commonly analgesic technique used in this surgery, using the same dose and volume of anaesthetics, allow improving the analgesic considerations.…”
Section: Discussionmentioning
confidence: 87%
“…The single local anaesthetic injection effectiveness for open shoulder surgery was previously poorly documented and not well defined [2,8,14], more data even if with discordant results have been reported that however were more related to the continuous infusion of anaesthetics and arthroscopic setting [5,9,[15][16][17]. Anyhow, a little clinical benefit of local infiltration was evidenced [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations